Knowledge sharing in a smoking cessation online community: a privacy calculus perspective - Chenglong Li; Hongxiu Li; Reima Suomi (United States, 2025)
The paper presents a study design intended to disentangle the various components of social support and
privacy concerns related to knowledge-sharing in a smoking cessation online health community from a
privacy calculus perspective. In the research model, social support confers benefits of informational
support, emotional support, esteem support, and network support, all of which have a positive effect on
knowledge-sharing behaviour therein. The privacy concerns, articulated in terms of risks, entail threat
appraisals (perceived severity and perceived vulnerability) and coping appraisals (response efficacy
and self-efficacy). Threat appraisals negatively affect knowledge-sharing in the smoking cessation
OHC, whereas coping appraisals have a positive effect on the sharing. Under privacy calculus theory,
the risk–benefit analysis determines individual users’ knowledge-sharing behaviour in a smoking
cessation OHC. The individual user’s smoking cessation OHC usage experience and the stage of
smoking cessation are set as moderators in the proposed research model to explore user differences in
knowledge sharing behaviour in the smoking cessation OHC. This study may contribute to a
comprehensive understanding of the core antecedents to knowledge-sharing in smoking cessation
OHCs.
Proceedings of the 27th European Conference on Information Systems (ECIS)